Pengaruh Financial Technology, Literasi Keuangan Dan Penggunaan Informasi Akuntansi Terhadap Kinerja UMKM - Alsyrah Indah Oktarini; Endang Kartini; Rusdi (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat (LP3M) Sekolah Tinggi Ilmu Ekonomi AMM (STIE AMM) Mataram, 2025)
This study aims to examine the influence of financial technology, financial literacy and the use of accounting information on the performance of MSMEs in Dompu Regency. So that the variables of this study consist of 3 (three) independent variables, namely financial technology (X1), financial literacy (X2) and the use of accounting information (X3) and the dependent variable, namely the performance of MSMEs (Y). The population of this study is MSME actors registered with the Dompu Regency Cooperatives and SMEs Office. Samples were taken using simple random sampling. Data was obtained by distributing 215 questionnaires to MSME respondents in Dompu Regency. The questionnaire that returned and could be used was 100 questionnaires. The data were analyzed using Multiple Linear Regression. The results of this study show that financial technology, financial literacy and the use of accounting information have a significant effect on the performance of MSMEs. The results of this study also show that the independent variables (financial technology, financial literacy and the use of accounting information) are able to explain the dependent variable (MSME performance) of 40.7% while the remaining 59.3 is influenced by other variables outside the regression model used in this study.